The nuclear and organellar tRNA-derived RNA fragment population in Arabidopsis thaliana is highly dynamic. Issue 6 (29th November 2016) - Cognat, Valérie; Morelle, Geoffrey; Megel, Cyrille; Lalande, Stéphanie; Molinier, Jean; Vincent, Timothée; Small, Ian; Duchêne, Anne-Marie; Maréchal-Drouard, Laurence
Abstract: In the expanding repertoire of small noncoding RNAs (ncRNAs), tRNA-derived RNA fragments (tRFs) have been identified in all domains of life. Their existence in plants has been already proven but no detailed analysis has been performed. Here, short tRFs of 19–26 nucleotides were retrieved from Arabidopsis thaliana small RNA libraries obtained from various tissues, plants submitted to abiotic stress or fractions immunoprecipitated with ARGONAUTE 1 (AGO1). Large differences in the tRF populations of each extract were observed. Depending on the tRNA, either tRF-5D (due to a cleavage in the D region) or tRF-3T ( via a cleavage in the T region) were found and hot spots of tRNA cleavages have been identified. Interestingly, up to 25% of the tRFs originate from plastid tRNAs and we provide evidence that mitochondrial tRNAs can also be a source of tRFs. Very specific tRF-5D deriving not only from nucleus-encoded but also from plastid-encoded tRNAs are strongly enriched in AGO1 immunoprecipitates. We demonstrate that the organellar tRFs are not found within chloroplasts or mitochondria but rather accumulate outside the organelles. These observations suggest that some organellar tRFs could play regulatory functions within the plant cell and may be part of a signaling pathway.